2021
DOI: 10.15406/ppij.2021.09.00326
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of ethanolic extract of Annona muricata against different pro-oxidant induced lipid peroxidation in rat brain and liver

Abstract: Annona muricata belongs to the family Annonaceae, which is rampant in the tropical and subtropical regions of the globe such as North America, Africa, Thailand and Asia. 1 Several pharmacological activities such as anti-inflammation, anti-diabetes, hepatoprotective and countless other benefits have been attributed to the extracts from the plant. [2][3][4][5][6][7] The phytoconstituents residing in the plant exhibit disease preventive properties, though they are not essential nutrients to human health. The plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the present study, two pro-oxidants, Fe 2+ and H 2 O 2 were employed in inducing lipid peroxidation in the liver and brain homogenates and the possible antioxidant effects of the extracts were evaluated. H 2 O 2 can be regarded as an effective oxidant of a large variety of biomolecules including lipids as research demonstrated that H 2 O 2 constituted a marked increase in lipid peroxidation in cerebral and hepatic tissues of rat [8,21,22]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, two pro-oxidants, Fe 2+ and H 2 O 2 were employed in inducing lipid peroxidation in the liver and brain homogenates and the possible antioxidant effects of the extracts were evaluated. H 2 O 2 can be regarded as an effective oxidant of a large variety of biomolecules including lipids as research demonstrated that H 2 O 2 constituted a marked increase in lipid peroxidation in cerebral and hepatic tissues of rat [8,21,22]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of several diseases such as diabetes, Parkinson disease and cancer is being mediated by lipid peroxidation. Reactive oxygen species (ROS) attack membrane lipids containing double bonds and abstract hydrogen atom, leading to the destruction of membrane lipids consequent to the formation of toxic hydroperoxides and lipid peroxyl radicals" [8]. "Lipid peroxidation is considered as the main molecular mechanisms involved in the oxidative damage to cell structures and in the toxicity process that lead to cell death.…”
Section: Introductionmentioning
confidence: 99%